Pine afforestation on degraded lands: a global review of carbon sequestration potential - Tudor, Ciprian; Constandache, Cristinel; Dinca, Lucian; Murariu, Gabriel; Badea, Nicolae Ovidiu; Tudose, Nicu Constantin; Marin, Mirabela (Frontiers in Forests and Global Change, 2025)
Pine plantations on degraded lands play an important role in providing ecosystem services, among the most significant being soil and land protection against erosion, water source protection, carbon sequestration, and the restoration of landscape and biodiversity. In addition, these plantations also have a significant social and economic role. This study offers a comprehensive bibliometric and systematic analysis of publications on the use of pines in plantations on degraded lands and the environmental effects of these plantations, especially regarding soil, water, carbon storage, and more. The study’s results include an assessment of research trends, key contributors, and their influence on scientific progress in forestry, ecological restoration, and environmental protection. A total of 281 publications on the use of pines in plantations on degraded lands were identified, published between 1983 and 2024. These publications mainly originate from the USA, China, and Spain, with additional contributions from European institutions. The research findings are published in top journals in the fields of forestry, ecology, and the environment, highlighting their global impact. These articles belong to the scientific fields of environmental science and ecology, forestry, agriculture, water sciences, and others. The research results have been published in numerous journals, with the most frequently cited being Forest Ecology and Management, Forests, and Land Degradation & Development. The most frequently used keywords include afforestation, forest, restoration, pine, and carbon. The analysis of publications on the use of pines for afforestation of degraded lands highlights the widespread use of pine species in reforestation, underlining the resilience and adaptability of these species in various degraded land conditions. Future research should focus on innovative techniques for ecological reconstruction and pine forest regeneration, measures to adapt these plantations to climate change, the impact of ecosystem management practices on degraded lands on their carbon storage potential, and the effectiveness of pine species in various ecological conditions.